Prevalence and barriers to health care transition for adolescent patients with childhood-onset chronic diseases across Japan: A nation-wide cross-sectional survey - Sakurai, Ikuho; Maru, Mitsue; Miyamae, Takako; Honda, Masataka (Frontiers in Pediatrics, 2022)
Since the Japan Pediatric Society published its “Recommendations on Transitional Care for Patients with Childhood-Onset Chronic Diseases” in 2014, there has been an increased interest in the health care transition of adolescents with childhood-onset chronic diseases in Japan. However, the actual status of healthcare transition were not studied yet. The purpose of this study was to explore the prevalence of transitional support for adolescent patients with childhood-onset chronic disease and the factors hindering their transition. We conducted an anonymous questionnaire survey in August 2020, targeting physicians and nurses involved in health care transition at 494 pediatric facilities in Japan. Survey items included demographic data, health care systems related to transition to adult departments, health care transition programs based on Six Core Elements (establishing transition policy, tracking and monitoring transition progress, assessing patient readiness for transition, developing the transition plan with a medical summary, transferring the patient, completing the transfer/following up with the patient and family), barriers to transition (34-item, 4-point Likert scale), and expectations in supporting transition (multiple-choice responses), which consisted of five items (78 questions); all questions were structured. Descriptive statistics were used for analysis. Of the 225 responses collected (45.5% response rate), 88.0% were from pediatricians. More than 80% of respondents transferred patients of 20 years or older, but only about 15% had took a structured transition process of four or more based on the Six Core Elements. The top transition barriers were "intellectual disability/rare disease" and "dependence on pediatrics" as patient/family factors, and "lack of collaboration with adult healthcare (relationship, manpower/system, knowledge/understanding)" as medical/infrastructure factors. The study provides future considerations, including the promotion of structured health care transition programs, development of transitional support tailored to the characteristics of rare diseases and disorders, and establishment of a support system with adult departments.